Safety evaluation of myostatin-edited Meishan pigs by whole genome resequencing analyses - Shanshan Xie; Lili Qian; Chunbo Cai; Shengwang Jiang; Gaojun Xiao; Ting Gao; Xiang Li; Wentao Cui (Czech Journal of Animal Science, 2019)
Genome editing technology can make specifically target genomic modifications, resulting in site specific DNA insertion, deletion or replacement in the genome of an organism. We have recently produced genetically engineered (GE) Meishan pigs containing a ZFN-edited myostatin (MSTN) loss-of-function mutation that leads to a clear "double muscle" phenotype as observed for Belgian cattle. In this study, whole genome resequencing was used as an approach to evaluate the safety risk, if any, associated with the introduction of a ZFN-edited myostatin (MSTN) loss-of-function mutation in a local pig breed, the Meishan pigs. The results of resequencing analyses show that the effective data from pigs of wild-type group and MSTN-edited GE group is greater than 99%. The 1× coverage rate is > 98%, and the 4× coverage rate is > 96%. The genetic variation on each chromosome is close to 1. From this whole genome resequencing study, our results demonstrated that 99.7% of single nucleotide polymorphisms (SNPs) are the same in the same genetic variation from both wild-type group and MSTN-edited GE group, implying genomic sequence variations are highly similar between the two groups of pigs.